2023
DOI: 10.1017/s0007123423000066
|View full text |Cite
|
Sign up to set email alerts
|

The Rich Have a Slight Edge: Evidence from Comparative Data on Income-Based Inequality in Policy Congruence

Abstract: Several recent studies have found unequal policy responsiveness, meaning that the policy preferences of high-income citizens are better reflected in implemented policies than the policy preferences of low-income citizens. This has been found mainly in a few studies from the US and a small number of single-country studies from Western Europe. However, there is a lack of comparative studies that stake out the terrain across a broader group of countries. We analyze survey data on the policy preferences of about 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…First, as largely acknowledged in research on participation and representation (e.g., Schwander, 2019, Persson andSundell, 2024), and consistent with similar work on income (Solt, 2008), a socioeconomic gap is also present regarding political engagement (thus supporting H1). There is a steady and robust gap in political engagement across income and education strata among the European countries under study for the three variables measuring engagement.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…First, as largely acknowledged in research on participation and representation (e.g., Schwander, 2019, Persson andSundell, 2024), and consistent with similar work on income (Solt, 2008), a socioeconomic gap is also present regarding political engagement (thus supporting H1). There is a steady and robust gap in political engagement across income and education strata among the European countries under study for the three variables measuring engagement.…”
Section: Discussionsupporting
confidence: 66%
“…The effect that the limited voice of those in the lowest strata of society has on political representation has been widely recognized. Mostly focusing on the USA, such studies have concluded that political decisions are systematically more responsive to top-income groups (Bartels, 2016;Persson and Sundell, 2024;Schakel and Van Der Pas, 2021). The poor tend to be more distant from the ideological stances of legislators than upper-income groups and to be less well represented, especially regarding economic issues (Giger et al, 2012;Rosset and Kurella, 2021;Lupu and Warner, 2022).…”
Section: The Interplay Between Socioeconomic and Political Inequalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth and finally, women tend to have lower incomes than men. As mentioned earlier, many studies have tested whether higher levels of income correspond to better policy representation, and though there is no consensus on this point (Elkjaer and Iversen 2020), most analyses find that affluence buys influence (Bartels 2016;Elsässer, Hense, and Schäfer 2021;Gilens and Page 2014;Persson and Sundell 2023).…”
Section: Theoretical Expectations and Hypothesesmentioning
confidence: 99%
“…Influential studies suggest that actual policymaking is disproportionally responsive to the preferences of more socioeconomically resourceful citizens (Gilens 2012;Elsässer and Schäfer 2023;Persson and Sundell 2023; but see also Elkjaer and Iversen 2020). Some segments of the population, often located towards the lower end of the socio-economic hierarchy, may thus feel excluded and frustrated with how governments are seemingly unwilling and/or ineffective in dealing with pressing insecurities and inequalities.…”
Section: Government Inefficacymentioning
confidence: 99%